Warning System Using Multicast Transmission for Pedestrian and Pedal-Cyclist Safety Against the Electric-Powered Driving Means in CVCN Network - Kim, Bachyun; Woo, Yoseop; Kim, Iksoo (International Journal of Engineering and Technology, 2018)
This paper deals with a warning system for the safety of pedestrians/pedal-cyclists against electric-powered driving means including hybrid/PHEV/EV/FCEV and electric wheel on minor roads. These roads are a subset of connected-vehicle communication network(CVCN). The fatalities of pedestrians/pedal-cyclists declined recently compared to the early 2000s, but fatality rate of vehicle accidents is increasing. Clearly, this phenomenon will continue because of the increasing number of virtually silent hybrid/PHEV/EV/FCEV and electric wheels on the road.The hybrid/PHEV/EV/FCEV such as green electric-powered ones that can reduce environmental pollution are much more dangerous than traditional vehicles to pedestrians/pedal-cyclists on minor roads. The main risk factor of the electric-powered vehicles is that they are very quiet on the road because of the use of electric motor instead of engine. Thus, the safety warning system that can notify pedestrians/pedal-cyclists the dangerous approaches of vehicles from their behind have to be provided on minor roads.The proposed framework for safety warning system using multicast informs pedestrians/pedal-cyclists through smartphone when electric powered driving means are closing from their behind on minor roads. This is a new technology that uses vibration or sound of smartphone instead of artificial noise generation which is equipped to the electric powered driving means recently.Â Â